The Effect of Giving Ginger Aromatherapy on Nausea and Vomiting in Cancer Patients Post Chemotherapy at Grandmed Hospital Lubuk Pakam - Syatria wati; Pratiwi Christa Simarmata; Debi Dinha Octora Sitepu; Dini Anggraini (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Cancer is one of the diseases that is the main cause of death in many parts of the country. In treating this disease, it can be done through chemotherapy, which can destroy cancer cells. However, there are side effects that can be felt by patients, namely nausea and vomiting. These symptoms can interfere with the patient's quality of life so that they become less compliant in following the next therapy. To overcome this nausea and vomiting condition, a type of non-pharmacological therapy can be tried, such as giving ginger aromatherapy which is known to contain active compounds such as gingerol and shogaol which can relieve these symptoms. Quantitative research with a Quasy Experiment design with a One Group Pretest Posttest approach was chosen in this research. A sample of 23 people was determined using the purposive sampling method. Analysis was carried out on the characteristics of respondents and the effect of ginger aromatherapy on nausea and vomiting was tested using a paired sample t-test. The results showed a change in the mean value from 4.52 to 2.48 or a decrease of 2.04, with a t value of 4.97, and a p value of 0.000 which can be interpreted that ginger aromatherapy can reduce the level of nausea and vomiting in cancer patients after aromatherapy. Ginger aromatherapy has been proven to reduce nausea and vomiting levels, making it suitable for recommendation for cancer patients after chemotherapy, so it can provide comfort and improve the patient's quality of life.